2013
DOI: 10.1016/j.aquatox.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

No substantial changes in estrogen receptor and estrogen-related receptor orthologue gene transcription in Marisa cornuarietis exposed to estrogenic chemicals

Abstract: HighlightsER and ERR transcription levels were unaffected in Marisa cornuarietis exposed to 17β-estradiol or 4-tert-Octylphenol.The mollusc ER protein interacts with the phytoestrogen genistein in transfected HEK-293 cells.The mollusc ERR protein interacts weakly with bisphenol-A in transfected HEK-293 cells.The mollusc ER protein binds to the vertebrate consensus estrogen response element (ERE) sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The phylogenetic position of the mollusc ER homologue with the vertebrate ER is well supported with a BMCMC posterior probability of 98% and bootstrap values of 0.88 and 0.79 ( Fig 1 ), supporting the suggestion that vertebrate and invertebrate ER diverged from a common ancestor, before the evolution of the deuterostomes [ 38 , 75 , 80 ]. Structural similarities between ER DBDs of molluscs, annelids, cephalochordates and vertebrates have been documented showing them to bind to and regulate transcription through estrogen response elements [ 36 , 40 , 74 , 81 , 82 ]. The ER LBD in invertebrates may have unique functions, since the mollusc ER homologue, at least in vitro (usually in mammalian reporter cell lines), appears to activate transcription constitutively in the absence of a ligand [ 36 , 37 , 39 , 40 ] although in annelids the ER has been shown to activate transcription in the presence of estrogens [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic position of the mollusc ER homologue with the vertebrate ER is well supported with a BMCMC posterior probability of 98% and bootstrap values of 0.88 and 0.79 ( Fig 1 ), supporting the suggestion that vertebrate and invertebrate ER diverged from a common ancestor, before the evolution of the deuterostomes [ 38 , 75 , 80 ]. Structural similarities between ER DBDs of molluscs, annelids, cephalochordates and vertebrates have been documented showing them to bind to and regulate transcription through estrogen response elements [ 36 , 40 , 74 , 81 , 82 ]. The ER LBD in invertebrates may have unique functions, since the mollusc ER homologue, at least in vitro (usually in mammalian reporter cell lines), appears to activate transcription constitutively in the absence of a ligand [ 36 , 37 , 39 , 40 ] although in annelids the ER has been shown to activate transcription in the presence of estrogens [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Structural similarities between ER DBDs of molluscs, annelids, cephalochordates and vertebrates have been documented showing them to bind to and regulate transcription through estrogen response elements [ 36 , 40 , 74 , 81 , 82 ]. The ER LBD in invertebrates may have unique functions, since the mollusc ER homologue, at least in vitro (usually in mammalian reporter cell lines), appears to activate transcription constitutively in the absence of a ligand [ 36 , 37 , 39 , 40 ] although in annelids the ER has been shown to activate transcription in the presence of estrogens [ 82 ]. We also identified a single estrogen-related receptor (ERR) in both B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the ER and ERR homologs (CgNR3A and CgNR3B respectively) was at similar levels. Previous research in gastropod species showed differences in expression for male and female reproductive tissues and no differences for other tissues [ 85 , 86 , 91 ]. Nevertheless, gene expression was measured in whole individuals (not separated by tissue) and sex-dependent expression could still be neutralized by pooling of tissues (e.g., high expression in gonads, but low expression in mantle and vice versa).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang et al (2014) demonstrated that BPA down-regulated 17 b-hydroxysteroid dehydrogenases (17b-HSDs), which control metabolism of steroids and fatty acids in Mytilus galloprovincialis digestive gland. BPA also increased the expression of estrogen receptor (ER) and estrogen-related receptor (ERR) genes in the reproductive tissue of the gastropod snail, Marisa cornuarietis at high concentrations (>10 −5 M, Bannister et al, 2013).…”
Section: Discussionmentioning
confidence: 99%